Fine Needle Aspiration Cytology of Musculoskeletal Lesions - Khan, Shaukat Hayat; raA, Iffat; Haque, Anwar Ul; Kayani, Zayad Afzal (International Journal of Pathology, 2018)
Objectives: Study the role of fine needle aspiration cytology (FNAC) in diagnosis of musculoskeletal tumors andtumor like lesions.Study Design: Descriptive cross sectional .Place and Duration: Abbas Institute of Medical Sciences and Pathology department of AJKMC from July 2013-October 2014.Materials and Methods: Twenty three patients who presented in orthopedic surgery outpatient with history ofpain and swelling were examined along with radiological correlation. The fine needle aspirations were performedsubsequently on a suitable site in the swelling. The smears were examined by a consultant pathologist with specialinterest in cytopathology.Results: The adequate aspirates (22/23) contained well preserved individual as well as clusters of cells displayingthe morphological features identical to the histopathological features making it possible to render definite diagnoses.The diagnoses represented broad spectrum of inflammatory, benign and malignant neoplastic lesions.Conclusion: Fine Needle Aspiration Cytology of osseous and soft tissue lesions is quite accurate and rewardingas it may obviate unnecessary surgery in some cases and may help in planning the surgery in other cases.